2008
DOI: 10.1239/aap/1222868179
|View full text |Cite
|
Sign up to set email alerts
|

Random Laguerre tessellations

Abstract: A systematic study of random Laguerre tessellations, weighted generalisations of the well-known Voronoi tessellations, is presented. We prove that every normal tessellation with convex cells in dimension three and higher is a Laguerre tessellation. Tessellations generated by stationary marked Poisson processes are then studied in detail. For these tessellations, we obtain integral formulae for geometric characteristics and densities of the typical k-faces. We present a formula for the linear contact distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
101
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(102 citation statements)
references
References 64 publications
1
101
0
Order By: Relevance
“…Concerning materials science, great interest has been devoted to the application of convex tessellation models, in which the grains are convex polyhedra; see, e.g., Lyckegaard et al (2011). The simplicity of these models allows a simple evaluation of size and shape characteristics of the grains (Lautensack and Zuyev, 2008) and relatively fast and accurate fitting to empirical data (Spettl et al, 2016). However, in connection with recent progress in microscopic research, the interest of scientists has significantly increased regarding more general tessellations with curved boundaries, which can better describe real grain shapes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning materials science, great interest has been devoted to the application of convex tessellation models, in which the grains are convex polyhedra; see, e.g., Lyckegaard et al (2011). The simplicity of these models allows a simple evaluation of size and shape characteristics of the grains (Lautensack and Zuyev, 2008) and relatively fast and accurate fitting to empirical data (Spettl et al, 2016). However, in connection with recent progress in microscopic research, the interest of scientists has significantly increased regarding more general tessellations with curved boundaries, which can better describe real grain shapes.…”
Section: Introductionmentioning
confidence: 99%
“…1 is a function of both the points' locations and their additional parameters (marks). A first extension of the Voronoi tessellation is the Laguerre tessellation or power diagram; see Lautensack and Zuyev (2008). Its generating marked point pattern is P = {x i , w i } ⊆ R 3 × R, and the distance measure is given as…”
mentioning
confidence: 99%
“…An important generalization is the Laguerre tessellation, also called power diagram, which employs weighted generator points and uses the power distance to measure the proximity of points; see, e.g., [1,2,3]. It has been shown that many convex tilings in three or more dimensions are Laguerre tessellations (see [3]), and also in two dimensions Laguerre tessellations are common.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that many convex tilings in three or more dimensions are Laguerre tessellations (see [3]), and also in two dimensions Laguerre tessellations are common. In addition, Voronoi tessellations in a number of nonEuclidean geometries can be represented as Laguerre tessellations (see [4]).…”
Section: Introductionmentioning
confidence: 99%
“…Cowan [43], [44], using ergodic theory, analyzed mosaic processes and Poisson point processes. Lautensack and Zuyev [45] evaluated Laguerre tessellations, which are weighted generalizations of Voronoi tessellations. To the best of our knowledge, the properties of random Voronoi diagrams for discrete graphs have not been investigated previously.…”
mentioning
confidence: 99%